The Role of Parents in Overcoming Adolescent Moral Crisis In Wairbleler Village, Waigete District, Sikka Regency - Mahmud, Syafriansah; Kasim, Abdul Muis; Nuwa, Gisela (EDUCTUM: Journal Research, 2023)
The role of parents is one of the roles not only as the head of the family, earning a living but the function of parents is also to educate, by instilling moral values, and parents exemplify positive behavior to adolescents. Good citizens must have good citizenship in the formation of positive young people's behavior, starting from the family implementing the religious guidance of parents in dealing with the moral crisis of adolescents. "The factors causing the moral crisis of youth in Wairbleler Village include family, economic, social environment and peer factors. So, with the moral crisis experienced by adolescents, the role of parents is needed. "Because the role of parents is the first and main guide in the family who are always closely related to teenagers, so they have a very big influence on teenagers. The life of today's youth is far from being touched by religion; this is also one of the factors in the occurrence of a teenage moral crisis. Therefore, the role of parents is very necessary in overcoming various crises, one of which is a moral crisis that occurs due to weak parental supervision. So, the role of parents is very important in guiding children, caring for children, and protecting children. The role of parents, especially in the Wairbeler village community, is to instill moral values, provide religious values, provide education and control oversight